Near-field spectroscopic investigation of dual-band heavy fermion metamaterials. Issue 1 (December 2017) - Gilbert Corder, Stephanie; Chen, Xinzhong; Zhang, Shaoqing; Hu, Fengrui; Zhang, Jiawei; Luan, Yilong; Logan, Jack; Ciavatti, Thomas; Bechtel, Hans; Martin, Michael; Aronson, Meigan; Suzuki, Hiroyuki; et al.
Abstract Broadband tunability is a central theme in contemporary nanophotonics and metamaterials research. Combining metamaterials with phase change media offers a promising approach to achieve such tunability, which requires a comprehensive investigation of the electromagnetic responses of novel materials at subwavelength scales. In this work, we demonstrate an innovative way to tailor band-selective electromagnetic responses at the surface of a heavy fermion compound, samarium sulfide (SmS). By utilizing the intrinsic, pressure sensitive, and multi-band electron responses of SmS, we create a proof-of-principle heavy fermion metamaterial, which is fabricated and characterized using scanning near-field microscopes with <50 nm spatial resolution. The optical responses at the infrared and visible frequency ranges can be selectively and separately tuned via modifying the occupation of the 4f and 5d band electrons. The unique pressure, doping, and temperature tunability demonstrated represents a paradigm shift for nanoscale metamaterial and metasurface design. Understanding the electromagnetic responses at subwavelength scales is important for achieving tunability. Using a combination of the near-field and far-field spectroscopy, the authors demonstrate a heavy fermion metamaterial with tunable dual-band optical responses by selectively and separately modifying the 4f and 5d band electrons.